Paroxetine and Mortality in Heart Failure: A Retrospective Cohort Study - Xu, Hongxuan; Meng, Lingbing; Long, Huanyu; Shi, Yueping; Liu, Yunqing; Wang, Li; Liu, Deping (Frontiers in Cardiovascular Medicine, 2022)
Abstract Introduction: Paroxetine is a GRK2 inhibitor that has been widely used to treat depression and anxiety over the last few decades. The inhibition of GRK2 has been studied extensively in vivo; however, evidence of its impact on heart failure remains scarce. Method: To assess the association between paroxetine use and mortality in patients with heart failure. We conducted a retrospective longitudinal cohort study from 2008 to 2019, with a follow-up time of 28 days for all groups. This is a single-center study using the Medical Information Mart for Intensive Care IV database with 11,657 heart failure patients identified. We performed genetic matching to adjust for the covariates. Heart failure patients prescribed paroxetine for >24 h after hospital admission were categorized into the paroxetine group (77 patients), with remaining heart failure patients making up the matched control group (231 patients). The primary outcome was 28-day all-cause mortality from the date of hospital admission. Secondary outcomes included length of intensive care unit stay, length of hospital stay, and in-hospital mortality. The Kaplan–Meier survival estimator, logistic regression, Cox regression, and restricted mean survival time were used to detect the association between paroxetine therapy and outcomes. Results: Patients who received paroxetine during one hospital admission lived, on average, 0.7 lesser days (95% CI -2.53-1.1, p=0.46) than patients who did not use it in a 28-day truncation time point. Multivariable logistic regression, including all matched covariates, demonstrated that the adjusted odds ratio of 28-day mortality of the paroxetine administration group was 1.1 (95% CI 0.37–2.9, p=0.90). Multivariable Cox regression of 28-day mortality presented an adjusted hazard ratio of 1.00 (95% CI 0.42-2.62, p=0.92). Paroxetine was associated with an increased survival time at a 3000-day truncation time point (203 days, 95% CI -305.69-817.8, p=0.37). Conclusions: In patients with heart failure, treatment with paroxetine did not significantly reduce 28-day all-cause mortality.